2024
DOI: 10.1111/tpj.16726
|View full text |Cite
|
Sign up to set email alerts
|

Loss of daylength sensitivity by splice site mutation in Cannabis pseudo‐response regulator

Keegan M. Leckie,
Jason Sawler,
Paul Kapos
et al.

Abstract: SUMMARYPhotoperiod insensitivity (auto‐flowering) in drug‐type Cannabis sativa circumvents the need for short day (SD) flowering requirements making outdoor cultivation in high latitudes possible. However, the benefits of photoperiod insensitivity are counterbalanced by low cannabinoid content and poor flower quality in auto‐flowering genotypes. Despite recent studies in cannabis flowering, a mechanistic understanding of photoperiod insensitivity is still lacking. We used a combination of genome‐wide associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Two recent mapping studies have suggested C. sativa homologues of APETALA2 and PSEUDO-RESPONSE REGU-LATOR 37 (PRR37) as candidate genes within Autoflower1 (Garfinkel et al, 2023;Leckie et al, 2023). Alterations of PRR37 homologues in T. aestivum, O. sativa, and Sorghum bicolor are known to confer photoperiod insensitivity due to de-repressed FT expression (Beales et al, 2007;Koo et al, 2013;Murphy et al, 2011).…”
Section: Photoperiod Insensitivity Originated Multiple Times Independ...mentioning
confidence: 99%
“…Two recent mapping studies have suggested C. sativa homologues of APETALA2 and PSEUDO-RESPONSE REGU-LATOR 37 (PRR37) as candidate genes within Autoflower1 (Garfinkel et al, 2023;Leckie et al, 2023). Alterations of PRR37 homologues in T. aestivum, O. sativa, and Sorghum bicolor are known to confer photoperiod insensitivity due to de-repressed FT expression (Beales et al, 2007;Koo et al, 2013;Murphy et al, 2011).…”
Section: Photoperiod Insensitivity Originated Multiple Times Independ...mentioning
confidence: 99%